PENGARUH KEBIJAKAN SUKU BUNGA BANK INDONESIA (BI Rate) TERHADAP NILAI TUKAR RUPIAH DAN RENTABILITAS BANK - Meliza SE.M.Com (LPPM Universitas Pekalongan, 2014)
Global economic crisis in some European countries and United States has affected the value of rupiah exchange rate. Depreciation of rupiah caused some industrial sectors that used imported raw material face high production cost. Therefore, Bank Indonesia as central bank takes some actions to save rupiah value by increasing the interest rate in order to raise capita inflow to Indonesia. This governance will also influence the banking sector especially the fluctuation of bank’s cost of fund and loan interest and eventually affect bank’s rentability. The data of Indonesia Interest rate and Rupiah exchange rate is derived from Bank Indonesia Website. Meanwhile, the data of bank’s rentability (Return on Assets) is derived from publicity of income statement and balance sheet of Bank Rakyat Indonesia and Bank Danamon period July 2010-July 2013. Furthermore, this research use multiple regression method as research methodology that measure the influence of interest rate to rupiah exchange rate and bank’s rentability period July 2010-July 2013. The analysis data results that movement of interest rate of Bank Indonesia (BI Rate) has influence to rupiah exche rate about 48,4%. However, it does not have significant influence to bank’s rentability or only about 30%. Keywords : interest rate, rupiah exchange rate, bank’s rentability